Guinea grass (Megathyrsus maximus) agronomic performances in mixed cultivation using irrigation condition, North-Western Ethiopia - Mihret Anteneh Wolele; Fentahun Meheret Zeleke; Yeshambel Mekuriaw Chekol; Bimrew Asmare Limenih; Zemenu Birhan Zegeye (PLoS ONE, 2025)
In this field experiment, the agronomic performance of Guinea grass was evaluated to assess the optimum planting spacing and harvesting age in mixed cultivation under irrigation conditions. These factors were arranged according to a 3*3 factorial setting, which was fitted to a randomized complete block design and replicated three times. This trial used three planting spaces (20, 30 and 40 cm) and harvesting ages (60, 90 and 120 days), grown in a mixed cropping system with Silver leaf desmodium using a furrow irrigation. The collected data includes plant height, leaves per plant, leaf length per plant, leaf to stem ratio, number of tillers per plant, number of roots per plant, root length per plant, and dry matter yield. The results of the study showed that age at harvest and planting space had a significant (P<0.001) effect on the morphological characteristics and dry matter yield of Guinea grass. The effect of these management practices was also affected the dry matter, crude protein and crude fiber contents of the grass. The maximum performances (high records) of the morphological characteristics and dry matter yield of Guinea grass were obtained by allocating a planting space of 40 cm and prolonging the harvesting period up to 120 days. However, harvesting at 90 days (11.48% of crude protein) resulted in the optimum nutritional contents. Therefore, in the area with irrigation facilities at midland agroecology, a planting space of 40 cm and a harvesting time of 90 days could be suggested through irrigation application in the study area and similar agro-ecologies.